In-vitro evaluation of antibacterial potential of cyanoacrylate tissue adhesives for intraoral wound closure - Murtaza A Kaderi; K.B Menaka; Renuka M Metgud; Mugdha R Gharat; Priyanka S Naik; Jyoti M Ajbani; Pooja P Naik; Aditi Mahajani (Mashhad University of Medical Sciences, 2017)
Background: Cyanoacrylate tissue adhesives have been used as a substitute to silk for intraoral wound closure. Placement of sutures provides a corridor for accumulation of microorganisms into tissue which leads to infection. Cyanoacrylate-based adhesives exhibit many properties of an ideal wound closure agent, minimizing the problems generated by suturing thread. The antimicrobial properties of cyanoacrylates have been extensively assessed in other fields of medicine. However, there is a dearth in the literature on the antibacterial effect of cyanoacrylates in oral environment against oral microflora. Aim: To assess the antibacterial properties of two commonly used formulations of cyanoacrylate tissue adhesives against oral pathogens. Materials and Methods: Iso-amyl cyanoacrylate and a blend of n-butyl and 2-Octyl cyanoacrylates were applied on sterile filter paper discs and placed on culture plates. Plates for aerobic & anaerobic bacterial cultures were incubated in blood agar & Brain-Heart infusion agar respectively.Following incubation period, the bacterial inhibitory halos were measured in millimeters. In order to evaluate the bactericidal efficacy, samples were collected from the inhibitory halos and re-cultured on new bacterial culture plates. Antibacterial activity was assessed against five bacteria: A.actinomycetemcomitans, P.gingivalis, T.forsythia, L.amylovorus and S.aureus. Statistical analysis used:  The data collected was analysed using Mann Whitney u test. Results: Cyanoacrylates demonstrated potent inhibitory effects against all test organisms. The zones of inhibition against gram positive bacteria were found to be larger than gram negative bacteria. The bactericidal activity of Iso amyl cyanoacrylate was found to be more potent than n-butyl + 2 octyl cyanoacrylate. Conclusions: Due to its potent antibacterial properties, cyanoacrylate tissue adhesives can be considered as appealing alternatives to silk sutures for intraoral wound closure and help prevent postoperative.